Baldomero Sanín Cano : Un intelectual humanista en el siglo XX. Prensa, modernidad y masificación (2013)
ABSTRACT: Baldomero Sanín Cano was one of the most relevant philosophers from Colombia in the 20th century. Although 150 years of his birth have passed, his works are still uncollected and many of his intellectual aspects are still unknown. The essay brings forth his intellectual profile focusing on the humanist aspect. Three registers of opinion and Colombian critical thought are exposed from unusual sources: journalistic convictions and his works in the press; an analysis on modernity; issues on the impact of the massification process. The sociological and political analysis, one of the most unknown fields, is also explored. The political and historical context of the creative production of Sanín Cano are also investigated, especially his writings in the newspapers La Nación of Buenos Aires and El Tiempo of Bogotá.